2021
DOI: 10.1007/s10751-021-01780-0
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic spin pumping via hyperfine interaction

Abstract: Spin pumping is an interfacial spin current generation from the ferromagnetic layer to the non-magnetic metal at its interface. The polarization of the pumped spin current s ∝ × ̇ depends on the dynamics of the magnetic moment . When the materials are based on light transition metals, mechanism behind the spin current transfer is dominated by the exchange interaction between spin of localized d-electrons and itinerant conduction electrons. In heavier transition metals, however, the interaction is not limited t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Furthermore, g damp comes from the nonequilibrium part of the response function, χ 2 , which is also responsible for damping-like spintransfer torque [42] and spin pumping [40]. Contribution of dipolar interaction in g damp is smaller than Fermi contact, in accordance with [47]. The value of the total g damp is in agreement with observation [45].…”
Section: Conclusion and Remarkssupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, g damp comes from the nonequilibrium part of the response function, χ 2 , which is also responsible for damping-like spintransfer torque [42] and spin pumping [40]. Contribution of dipolar interaction in g damp is smaller than Fermi contact, in accordance with [47]. The value of the total g damp is in agreement with observation [45].…”
Section: Conclusion and Remarkssupporting
confidence: 75%
“…A recent study demonstrated the spin-current pumping from nuclear spin waves [45,46]. In such a case, the spin transfer is mediated by the hyperfine coupling [47], which consists of dipole-dipole [5,48] and Fermi contact interactions [49].…”
Section: Introductionmentioning
confidence: 99%
“…While the spin pumping of Y 3 Fe 5 O 12 can be described by the dynamic of Fe magnetic moment alone [27], the total spin current generation of RY 2 Fe 5 O 12 require two magnetic sub-lattices model. Since the spin mixing conductance is shown to arise from the exchange interaction between the localized spin of ferromagnet and conduction spin of the non-magnetic metal [27,28,29…”
Section: Thermal Spin Pumping From Ferrimagnetmentioning
confidence: 99%
“…In linear response regime, the exchange interaction dictates that the spin density of the conduction electron responds linearly to perturbation due to exchange interaction [4,28] (r) = ∑…”
Section: Damping Torque Due To Interfacial Spin Mixingmentioning
confidence: 99%